2018
DOI: 10.1111/pbi.12926
|View full text |Cite
|
Sign up to set email alerts
|

Genome and evolution of the shade‐requiring medicinal herb Panax ginseng

Abstract: Summary Panax ginseng C. A. Meyer, reputed as the king of medicinal herbs, has slow growth, long generation time, low seed production and complicated genome structure that hamper its study. Here, we unveil the genomic architecture of tetraploid P. ginseng by de novo genome assembly, representing 2.98 Gbp with 59 352 annotated genes. Resequencing data indicated that diploid Panax species diverged in association with global warming in Southern Asia, and two North American species evolved via two intercontinental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(140 citation statements)
references
References 89 publications
7
123
0
Order By: Relevance
“…S10 ). Our results demonstrate that this WGD event occurred in the common ancestor of the studied Panax species, which is strongly supported by the tetraploid P. ginseng genome analysis that revealed such a shared WGD event in the Panax lineage at 28 MYA (Pg-β) 69 .…”
Section: Resultssupporting
confidence: 75%
“…S10 ). Our results demonstrate that this WGD event occurred in the common ancestor of the studied Panax species, which is strongly supported by the tetraploid P. ginseng genome analysis that revealed such a shared WGD event in the Panax lineage at 28 MYA (Pg-β) 69 .…”
Section: Resultssupporting
confidence: 75%
“…Published P . ginseng genome data indicates that Pg_scaffold6708 (aligned with Scaffold8624 sequecned in another study 6 ) and Pg_scaffold2289 harbor three and two PgUGT94 homolog sequences in tandem repeat arrays, respectively 5 . Our cloning and sequencing of a 14–26 kb fragment from Pg_scaffold6708 demonstrated that it contained three PgUGT94 homolog genes, which were identical to three detected PgUGT94 units (PgUGT94Q5-V1, PgUGT94Q11-V1, and PgUGT94Q4-V1) from the P .…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, we also sequenced and established the databases for the transcriptomes of the roots of 5-, 12-, 18- and 25-year-old plants [34] and the roots of four-year-old plants of 42 genotypes (named from S1 to S42) representing the diversity of Jilin ginseng [35]. In this study, a ginseng line IR826 genome sequence database [36] and another Ginseng Genome Database (http://ginsengdb.snu.ac.kr/index.php) reported by Kim et al [37] were also used. In addition, a transcriptome database of the adventitious roots of ginseng cv.…”
Section: Methodsmentioning
confidence: 99%